Huella de carbono generada por las actividades avícolas en la granja Velasco, Bahía de Caráquez - Vélez Velasco, Alejandro Javier (2021)
This research was carried out at the “Velasco” poultry farm, located in Bahía de Caráquez, Sucre canton, Manabí province; the same purpose is to estimate the carbon footprint generated by the activities of the poultry industry and thus propose alternative measures to reduce greenhouse gases. For the purpose of this work, the current environmental situation of the farm was established, with which it was possible to obtain information about the general data, operation and processes that are carried out in the poultry farm. Subsequently, the carbon footprint was calculated by multiplying the consumption of each activity by its emission factor, for this a calculator was used as a work tool using the Excel program; obtaining 110,910.55 kg CO2e / year as a result of the calculation in the 3 stages of egg production: Aging stage: 23.42%, laying stage: 74.57% and the distribution stage: 2.01%. Finally, alternative measures were established that would contribute to the reduction of greenhouse gases generated by the activities of the “Velasco” poultry farm.